2019
DOI: 10.32709/akusosbil.537650
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Evaluation of Violence Against Women: The Example of Sakarya

Abstract: Bu araştırma toplumumuzda yaygın olarak görülen kadına yönelik şiddetin erkek bakış açısıyla değerlendirilmesi üzerine kurgulanmıştır. Aile içindeki tüm bireyler aile içi şiddete maruz kalmakla birlikte şiddetin merkezini kadın oluşturmaktadır. Araştırmanın genel amacı ve alt amaçları esas alınarak 210 evli erkeğe anket uygulanmıştır. Elde edilen veriler SPSS programında analiz edilmiş; frekans, Ki-Kare, Spearmon Rho, Bağımsız Örneklem t-Testi, Tek Yönlü Varyans ve Tek Yönlü ANCOVA analizleri uygulanmıştır. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Demir 15 reported that the education level of married men was a factor that affected men's attitudes towards violence against the body and identity; it was found that while men who graduated from primary school were not against violence against women, men who graduated from high school and university were against violence against women. Genç et al 19 reported that while high school and university graduates were against violence against women, men who graduated from | 887 primary school were not. A study that investigated the factors affecting men's physical violence against women reported no significant differences between marital status and violence against women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demir 15 reported that the education level of married men was a factor that affected men's attitudes towards violence against the body and identity; it was found that while men who graduated from primary school were not against violence against women, men who graduated from high school and university were against violence against women. Genç et al 19 reported that while high school and university graduates were against violence against women, men who graduated from | 887 primary school were not. A study that investigated the factors affecting men's physical violence against women reported no significant differences between marital status and violence against women.…”
Section: Discussionmentioning
confidence: 99%
“…Men who got married to their wives with their own will were against violence against women, and men who did not marry their wife with their own will were not against violence against women. Bora 13 and Genç et al 19 reported that men who got married with their wives with their own will and who had a companionate marriage were against violence against women. This finding of the study was in line with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Eşlerin eğitim seviyelerinin düşük olması kadına şiddet uygulama açısından bir risk faktörüdür (4). Bununla beraber, eğitim seviyesi yüksek olan erkekler şiddet türleri konusunda daha fazla duyarlı davranmaktadırlar (29). Eğitim seviyesinin yüksek olması, kişilerin etkin iletişim kurmalarına ve problem çözme becerilerini geliştirmelerine katkı sağlayabilmektedir.…”
unclassified